IDENTIFIKASI DAN PENENTUAN KONSENTRASI ION LOGAM Cr, Fe, Cu, Zn, Cd dan Pb PADA DEBU JALANAN DI SEKITAR KAWASAN MALIOBORO YOGYAKARTA - Allwar Allwar (Universitas Islam Indonesia, 2005)
ABSTRACTIdentification and determination of heavy metal ions Cr, Fe, Cu, Zn, Cd and Pb on the duststreet around Malioboro area have been done. Malioboro area is one of the shopping centre andpedestrian tourism place in Yogyakarta that is the most crowded area. In summer season,Malioboro was not pleasant to visit caused by dry and hot climate, crowded and smell of exhaustedautomobile. These reason have been used to select Malioboro as a place for collecting dustsample. The dust has been obtained from five different locations such as location A station Tugu,location B Mall Matahari, location C governor office, location D pasar Bringharjo and location Ecross section of pos office. The dust sample was analyzed to identify and determine its metal ionscontain Cr, Fe, Cu, Zn, Cd and Pb using Atomic Absorption Spectrophotometry. The result of thisexperiment show that the highest concentration of ion metals at each location are Cu 656,75μg/gat location A , Fe 548,16μg/g at location B, Fe 420,16μg/g at location C, Pb 729,16μg/g at locationD and Fe 652,16µg/g at location EKey words: Dust sample, Malioboro street, Cr, Fe, Cu, Zn, Cd and Pb, Atomic AbsorptionSpectrophotometry